Introductory Geography - Zimmer, Christopher (New York Syrawood Publishing House, 2020)
The field of study, which deals with features, lands, inhabitants and phenomena of the Earth and planets is known as geography. It seeks to understand the Earth, along with the natural and human complexities. The two broad divisions of geography are human geography and physical geography. The people and their communities, as well as their cultures and interactions with the environment are studied within human geography. The different processes and patterns in the natural environment such as the hydrosphere, biosphere, geosphere and atmosphere are studied within physical geography. Some of the tools used within this field of study are cartography, geographic information systems and remote sensing. This book provides significant information of this discipline to help develop a good understanding of geography and related fields. It includes contributions of experts and scientists which will provide innovative insights into this field. The book aims to serve as a resource guide for students and experts alike and contribute to the growth of the discipline
Keywords: Geography; Earth Sciences; Cosmography